X‐ray Photon Correlation Spectroscopy Studies of Surfaces and Thin Films. (18th September 2014) - Sinha, Sunil K.; Jiang, Zhang; Lurio, Laurence B.
<x xml:space="preserve">Abstract</x> The technique of X‐ray Photon Correlation Spectroscopy (XPCS) is reviewed as a method for studying the relatively slow dynamics of materials on time scales ranging from microseconds to thousands of seconds and length scales ranging from microns down to nanometers. We focus on the application of this technique to study dynamical fluctuations of surfaces, interfaces and thin films. We first discuss instrumental issues such as the effects of partial coherence (or alternatively finite instrumental resolution) and optimization of signal‐to‐noise ratios in the experiments. We then review what has been learned from recent XPCS studies of capillary wave fluctuations on liquid surfaces and polymer films, of nanoparticles used as probes to study the interior dynamics of polymer films, of liquid crystals and multilamellar surfactant films, and of metal surfaces, and magnetic domain wall fluctuations in antiferromagnets. We then discuss studies of non‐equilibrium dynamics described by 2‐time correlation functions. Finally, we briefly speculate on possible future XPCS experiments at new synchrotron sources currently under development including studies of dynamics on time scales down to femtoseconds.